Pengembangan Profesi Guru SD Pada Implementasi Kurikulum Merdeka Belajar - Cahya, Afina Dwi; Azizah, Farinka Nurahmah (IBTIDA-Jurnal Kajian Pendidikan Dasar, 2024)
Teachers have an important role in the growth and development of future generations. Teachers are still required to improve the quality of formal education, so that almost all educational reform efforts depend on teachers. Therefore, development activities are needed to improve the professional quality of educators. Criteria for assessing teacher professionalism include: ability to master material, manage PBM, manage classes, manage media or learning resources, master pedagogical foundations, and be familiar with teaching methods, teacher interactions, teaching and learning processes, student achievement assessments, familiarity with BP service functions and programs , and understanding of school management. Implementation of community service activities at SD Negeri 1 Baadia is a collaborative activity between SD Negeri 1 Baadia teachers and STKIP Pelita Nusantara Buton teachers in the context of developing teacher professionalism at the school and improving the quality of human resources in the school environment. Education World. The method for implementing community service is consultation or outreach to increase understanding and awareness of teacher professionalism in implementing independent learning programs. As a result of implementing community service activities, the teachers at SD Negeri 1 Baadia understand their duties, functions and roles in developing intelligent and capable students in accordance with the ideals of the independent learning curriculum.